Неразрушающий контроль магнитодиэлектрических и ферритовых образцов с металлической подложкой - Мизерник, В. Н.; Одаренко, Е. Н.; Шматько, А. А. (ХНУРЭ, 2010)
При промышленном производстве магнитодиэлектрических и ферритовых материалов с металлизированными поверхностями представляется важным определение параметров наполняющей среды и толщины слоя методами неразрушающего контроля с целью их использования в различных функциональных узлах СВЧ приборов, опто- и полупроводниковой электроники в микроволновой и миллиметровой области длин волн. Waveguide T-junction model for measurement of the material parameters and thickness of a single-layered gyrotropic medium with a metal substrate is considered. These parameters are derived through amplitude and a phase of the waveguide wave reflection coefficient. For this purpose the exact solution of the wave scattering problem on the T-junction of waveguides is obtained. Generally the problem solution is reduced to second kind linear algebraic equations system (LAES) concerning amplitudes of the waveguide waves in the area of waveguides connection. Dependences of amplitude and a phase of the waveguide wave reflection coefficient on various material parameters of the specimen and its thickness for the dielectric, magnetodielectric and ferrite media are represented.
Keywords: Т–образное сочленение волноводов; задача рассеяния волноводной волны